Consultoria empresarial - a carreira dos meus sonhos ou "A house of lies": a idealização da carreira do consultor de empresas por alunos de Engenharia de Produção - Sousa, Rodrigo dos Santos de (2018)
Following an evolutionary tendency of capitalism itself, the concept of flexibility applied to the career grows, as opposed to traditional careers, doing the workers take responsibility for the paths of their careers and for their employability. In this scenario, one profession that stands out is the career of the business consultant. It is seen by many as being highly flexible. Based on this, this dissertation aims to raise with students of Production Engineering their perceptions in order to understand the representations that they construct about the career focused on business consulting. The population of this study was composed of 300 undergraduate students of the Production Engineering in differents educational institutions. For his students a questionnaire with 30 qualitative questions was applied. The analysis of the questionnaire was performed using descriptive statistics and multivariate data analysis. By associating to the objectives of the work, in different phases, other methods became necessary, such as content analysis and interviews. The questionnaire was applied from March to May 2017, having obtained a total of 300 participations. In parallel, there was information search on the websites of the main multinational consultancies. In the survey it was verified that all the companies studied present in their websites, notably in the pages for recruitment, the discourse of flexibility, besides offering accelerated career growth, internal training program, international career proposal and specific programs for newly-formed. In the statistical analysis, 67% of the respondents were male, with the majority (57%) between 17 and 21 years of age. Using the statistical software SPSS V20, the KMO result was 0.771, enabling the factor analysis to be performed. Six factors were generated that were named according to the issue with the most weight in it. First the factors were analyzed according to the demographic data (gender, type of educational institution and age). The data confirm that there is a general average interest of the students in the consulting career (3,20), and the interest is higher among the students of private schools, there being no differentiation between gender or age group. The perception that the consultant's career is more flexible, dynamic and glamorous was also verified, with averages of 3.56, 4.23 and 2.76, respectively for each factor (flexible, dynamic and glamorous). The data and the interviews confirm that there is a greater interest of the students of Production Engineering by the consulting area. The students associate the career of consultant with the training received and perceive in her the possibility of living a flexible and dynamic characteristic.